Diagnostic value of 99mTc-MDP SPECT/spiral CT combined with three-phase bone scintigraphy in assessing suspected bone tumors in patients with no malignant history. Issue 7 (July 2015) - Zhang, Yiqiu; Shi, Hongcheng; Li, Beilei; Xiu, Yan; Cai, Liang; Gu, Yushen; Chen, Shuguang
<x xml:space="preserve">Abstract</x> Introduction Three-phase bone scintigraphy using technetium-99m-methylene diphosphonate is used to diagnose skeletal lesions, whereas single-photon emission computed tomography/computed tomography (SPECT/CT) improves the diagnostic accuracy of bone disease. We investigated the usefulness of SPECT/CT combined with three-phase bone scintigraphy over three-phase bone scintigraphy alone in assessing suspected bone tumors in patients with no malignant history. Materials and methods Forty-eight patients (30 men and 18 women; mean age, 43.3±20.1 years; age range, 11–82 years) with suspected bone tumors who underwent technetium-99m-methylene diphosphonate three-phase bone scintigraphy and SPECT/CT between July 2008 and August 2013 were retrospectively reviewed. The lesion from each patient was resected or biopsied for pathological confirmation of the diagnosis within 3 weeks of the bone scan. All images were interpreted by two experienced nuclear medicine physicians who had not been involved in the selection of data for the present study. The reviewers were aware of the patient's sex, age, and the lesion's site but were unaware of the results of other imaging modalities, such as radiography, MRI, and laboratory tests. In cases of discrepancy regarding the interpretations, a consensus was reached after mutual discussion. The diagnostic ability of three-phase bone scintigraphy and SPECT/CT combined with three-phase bone scintigraphy was compared with pathological results using the χ2-test, with P-values less than 0.05 indicating significant differences. Agreement between three-phase bone scintigraphy alone or SPECT/CT combined with three-phase bone scintigraphy with pathological results was evaluated using κ scores. Results Pathological results from the 48 lesions of all patients revealed 32 malignant bone tumors and 16 benign lesions. On using three-phase bone scintigraphy and SPECT/CT combined with three-phase bone scintigraphy for the differential diagnosis of bone lesions, we found sensitivities to be 96.9 and 100%, specificities to be 31.2 and 81.3%, positive predictive values to be 73.8 and 91.4%, and negative predictive values to be 83.3 and 100%, respectively. The diagnostic accuracies of three-phase bone scintigraphy alone and SPECT/CT combined with three-phase bone scintigraphy were 75.0 and 93.8%, respectively (χ2=5.057; P=0.025). κ scores for the agreement of three-phase bone scintigraphy and SPECT/CT combined with three-phase bone scintigraphy with pathological results were 0.333 (P=0.005) and 0.850 (P<0.0001), respectively. Conclusion Compared with three-phase bone scintigraphy, the diagnostic accuracy of SPECT/CT combined with three-phase bone scintigraphy was higher. SPECT/CT combined with three-phase bone scintigraphy is beneficial over three-phase bone scintigraphy for the differential diagnosis of suspected bone tumors in patients with no malignant history.